Pelatihan peningkatan kemampuan komunikasi bahasa inggris melalui co-trainers online program - Setyowati, Ratini; Sopingi, Sopingi (Nur Science Institute, 2021)
English Communication skills are needed by every graduate, especially vocational school graduates because the purpose of forming a vocational school is to create a young generation at the beginning of the workforce who is able to directly enter and be absorbed by the world of work. The purpose of this training is to improve the English communication skills of students of SMK Kesehatan Citra Nusantara Klaten through the online Co-Trainers program. The subjects in this training are students of SMK Kesehatan Citra Nusantara Klaten class XII who have been selected. There are 30 students who have been selected as training participants. The implementation of this training is carried out by providing training to improve English communication skills for prospective Co-Trainers, which is divided into several stages, namely introduction, implementation, and evaluation. The implementation material in this training is divided into three points, namely photographs, questions and responses, and sort conversations. The result of this training is English communication skills improvement measured by an oral test conducted with pre-test and post-test. The post-test results show that students are able to explain and describe photos/pictures well, use prepositions in sentences, respond to questions well, and are able to practice short conversations. Suggestions for SMK English teachers to focus on mastering English communication.